Network-Based Entrepreneurial Marketing Through Strategic Collaboration With Sez Singhasari: a Case Study of Animation Startups in Malang Raya - Suci, Rahayu Puji; Iswari, Hanif Rani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2025)
This study explores how creative startups in Malang Raya utilize entrepreneurial marketing strategies within the ecosystem of SEZ Singhasari—Indonesia’s first Special Economic Zone focused on digital and creative industries. While traditional marketing frameworks often fail to address the contextual needs of early-stage creative businesses, this research adopts a qualitative thematic approach to understand how collaboration, local value integration, and network-based bootstrapping enhance startup visibility, engagement, and differentiation. Using in-depth interviews with animation startup founders, the study identifies three key strategic patterns: (1) the role of SEZ infrastructure as a catalyst for resource optimization and lean marketing, (2) co-marketing through mutual digital platforms and network-based content creation, and (3) integration of local cultural narratives into branding to create culturally resonant products. These themes are discussed through the lens of entrepreneurial marketing theory, resource advantage theory, and cultural branding. Findings suggest that SEZ Singhasari plays a significant enabling role by facilitating co-created campaigns, shared branding platforms, and cultural legitimacy—allowing bootstrapped startups to compete beyond resource limitations. The study highlights that marketing within creative economies is not only a transactional function but also a social and cultural process, shaped by ecosystemic interdependence. Practical implications are offered for SEZ planners, creative policymakers, and local entrepreneurs seeking to foster sustainable, place-based business strategies.